PASAR KERJA FLEKSIBEL VERSUS PERLINDUNGAN PEKERJA DI INDONESIA - Zantermans Rajagukguk (Research Centre for Population, Indonesian Institute of Sciences, 2010)
Some empirical studies have tried and showing that labor market in most of countries outside of Europe and USA, are inflexible, or rigid. One of the most relevant causes is connected with rigidities of employment protection legislation (EPL). Theoretically it said that any kind of EPL will prevent employers to hiring and .firing employee. So, to create LMF, an argument which is raised is addressed to abolish EPL. This paper aimed to suggests the analysis of (1) the impact of applying the concept of LMF connected with the employment protection in Indonesia, especially those related to wages, employment status, trade union, and layoffs, (2) the most appropriate form of LMF due to Indonesia s conditions. This paper is part of the review on